Onward maths textbook 2 (the city school special edition) - Hawa Shahbal; Sim, Penny Edgar, Katharine (Alston Publishing House Pte Ltd Singapore, 2014)
The "Onward Maths 2, Textbook" is designed for primary students to build on their mathematical understanding. It covers a range of topics, including advanced addition and subtraction, multiplication, division, fractions, and basic geometry. The textbook employs clear explanations, illustrative examples, and step-by-step problem-solving strategies to help students grasp concepts effectively. With a focus on critical thinking and real-life applications, it aims to engage students and foster a strong foundation in mathematics as they progress through their education.